A comparative study on the motivated consumer innovativeness of drone food delivery services before and after the outbreak of COVID-19. Issue 4 (4th May 2021) - Hwang, Jinsoo; Choe, Ja Young; Choi, Young Gin; Kim, Jinkyung Jenny
ABSTRACT: This study sought to identify the importance of motivated consumer innovativeness through the moderating role of the COVID-19 outbreak in the context of drone food delivery services. The data were collected from the different periods that are before and after the COVID-19 outbreak, respectively. The structural equation modeling analysis showed that three sub-dimensions of motivated consumer innovativeness, such as functional, hedonic, and social motivations, positively affected attitude toward drone food delivery services. In addition, the attitude had a positive influence on intentions to use the services. Furthermore, the outbreak of COVID-19 moderated the relationship between functional motivation and attitude.